PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN (Studi Empiris Sektor Properti dan Real Estate yang Terdaftar di BEI Periode 2019-2021) - Risma Pravita Indriani; Chairil Anwar (Bajang Institute, 2022)
This study aims to find out the significant effect of profitability on the timeliness of financial statement submission, the significant effect of liquidity on the timeliness of financial statement submission, the significant effect of company size on the timeliness of financial statement submission, and the simultaneous significant influence between profitability, liquidity, and firm size on the timeliness of financial report submission. The research method used is descriptive quantitative method using data analysis tool SPSS (Statistical Program for Social Science) IBM version 23, to measure timeliness as the dependent variable, profitability, liquidity, company size as independent variables. The sampling method is non-probability sampling purposive sampling type, then obtained samples during the study period as many as 33 of 11 companies. The results of this study indicate that profitability and liquidity have no significant effect on timeliness, while company size significantly affects the timeliness of financial report submission. In addition, the independent variables have a significant simultaneous effect on the timeliness of submitting financial reports